2023
DOI: 10.5398/tasj.2023.46.1.74
|View full text |Cite
|
Sign up to set email alerts
|

Performance, Methane Emission, Nutrient Utilization, and the Nitrate Toxicity of Ruminants with Dietary Nitrate Addition: A Meta-analysis from In Vivo Trials

Abstract: This study aims to evaluate the effects of dietary nitrate addition on performance, methane emission, nutrient utilization, and the nitrate toxicity of ruminants by using the meta-analysis methodology from in vivo trials. A total of 38 published papers and 139 studies were used. Parameters observed were feed intake, animal performance, enteric methane emission, and nitrate toxicity. Data were subjected to the mixed model methodology. Nitrate doses or forms were treated as fixed factors, while the different stu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
0
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 35 publications
0
0
0
Order By: Relevance
“…Meanwhile, Methane is the result of rumen fermentation produced by methanogenic bacteria by utilizing carbon dioxide and hydrogen. By adding nitrate at the right dose, nitrate compounds will use hydrogen in the reduction process to ammonia, so that the substrate for methane production is reduced [3]. However, the addition of urea nitrate in this study did not significantly reduce the total gas and methane production (Table 3).…”
Section: Resultsmentioning
confidence: 62%
See 1 more Smart Citation
“…Meanwhile, Methane is the result of rumen fermentation produced by methanogenic bacteria by utilizing carbon dioxide and hydrogen. By adding nitrate at the right dose, nitrate compounds will use hydrogen in the reduction process to ammonia, so that the substrate for methane production is reduced [3]. However, the addition of urea nitrate in this study did not significantly reduce the total gas and methane production (Table 3).…”
Section: Resultsmentioning
confidence: 62%
“…On the other hand, nitrate is a source of NPN which can be added to ruminant feed such as urea. Previous research has shown that nitrate acts as a hydrogen acceptor during methanogenesis [3]. Nitrate compounds are reduced by rumen bacteria to nitrite in a short time and then converted into ammonia which is used for microbial protein synthesis.…”
Section: Introductionmentioning
confidence: 99%